The Unity Of The Aramaic Acts - Wilson, William J. (Harvard theological review, 1918)
The most interesting contribution to New Testament criticism in recent times has come from a scholar in another field. Professor Torrey, a student of Semitics and particularly of the Aramaic, the language of the common people in Palestine before and after the Christian era, has propounded a new theory regarding the Book of Acts. Chapters 1 1b —15 35 are thought by him to have comprised an Aramaic book written about 49 or 50 A.D., which Luke later procured in Palestine and translated as faithfully as he was able, at the same time adding the remaining chapters himself in Greek on the basis of his own knowledge and investigation. The two parts of the book are accordingly designated I and II Acts, respectively. The evidence for the hypothesis is primarily linguistic. A striking series of Aramaisms and of mistranslations which can be plausibly corrected on the basis of the Aramaic, is found in I Acts, while in II Acts the reflections of Aramaic idiom are rare and instances of mistranslation are wholly lacking. The literature of the subject is not yet large, but a careful résumé and discussion of the new theory has appeared from the pen of Professor Foakes-Jackson. Since he questions the validity of Professor Torrey's more important deductions—conclusions whose correctness had been accepted almost without qualification by the present writer—a further consideration of their claims to credence may be permissible.